Determination of neurotoxic agents as markers of common vetch adulteration in lentil by LC-MS/MS. (15th April 2017) - Ghasemi, Nesa; Secen, Hasan; Yılmaz, Hasibe; Binici, Burcu; Goren, Ahmet C.
Highlights: LC-IDMS/MS method for determination of β-cyanoalanine in lentil samples. LC-MS/MS method with internal standard quantitation for γ-glutamyl-β-cyanoalanine determination in lentil. Presenting method validation, traceability and uncertainty calculation. Determination of adulteration in lentil. Abstract: Vicia sativa (common vetch), which contains β-cyanoalanine (BCA) and γ-glutamyl β-cyanoalanine (γGBCA) is used for adulteration of lentil and have neuro toxic effects on people and animals. Therefore the determination of BCA and γGBCA analytes in accurate and reliable manner has high importance for human and animal health. LC-IDMS/MS method has been developed and validated for quantitative analyses of β-cyanoalanine and 13 C labeled BCA is used as an internal standard in γGBCA analysis. In order to validate the method, linearity, recovery, precision (repeatability), intermediate precision, limit of detection, and limit of quantification parameters were investigated. The correlation coefficient was found to be greater than 0.99 for both analytes. The recoveriess were determined as 95.8% for BCA and 97.4% for γGBCA. The relative expanded measurement uncertainties of β-cyanoalanine and γ-glutamyl-β-cyanoalanine were obtained as 4.6% and 5.8%, respectively with the coverage factor, k, is 2 and at 95% confidence level.